Personifying the spirit of women... A garden dedicated to fairer sex - Sheela, V.L. (Indian Horticulture, 2015)
The garden was a pleasant surprise and brought nostalgic memories to the author as a beloved teacher of her school days who inspired her towards athletic achievements and win laurels for her alma mater was called Sister Mary Zoe.